Charge versus Energy Transfer Effects in High-Performance Perylene Diimide Photovoltaic Blend Films - Singh, Ranbir R.; Shivanna, Ravichandran; Iosifidis, Agathaggelos; Butt, Hans Jürgen; Floudas, George A.; Narayan, K. S.; Keivanidis, Panagiotis E. (My University, 2015)
Perylene diimide (PDI)-based organic photovoltaic devices can potentially deliver high power conversion efficiency values provided the photon energy absorbed is utilized efficiently in charge transfer (CT) reactions instead of being consumed in nonradiative energy transfer (ET) steps. Hitherto, it remains unclear whether ET or CT primarily drives the photoluminescence (PL) quenching of the PDI excimer state in PDI-based blend films. Here, we affirm the key role of the thermally assisted PDI excimer diffusion and subsequent CT reaction in the process of PDI excimer PL deactivation. For our study we perform PL quenching experiments in the model PDI-based composite made of poly[4,8-bis(5-(2-ethylhexyl)thiophen-2-yl)benzo[1,2-b;4,5-b′]dithiophene-2,6-diyl-alt-(4-(2-ethylhexanoyl)-thieno[3,4-b]thiophene)-2-6-diyl] (PBDTTT-CT) polymeric donor mixed with the N,N′-bis(1-ethylpropyl)-perylene-3,4,9,10-tetracarboxylic diimide (PDI) acceptor. Despite the strong spectral overlap between the PDI excimer PL emission and UV-vis absorption of PBDTTT-CT, two main observations indicate that no significant ET component operates in the overall PL quenching: the PL intensity of the PDI excimer (i) increases with decreasing temperature and (ii) remains unaffected even in the presence of 10 wt % content of the PBDTTT-CT quencher. Temperature-dependent wide-angle X-ray scattering experiments further indicate that nonradiative resonance ET is highly improbable due to the large size of PDI domains. The dominance of the CT over the ET process is verified by the high performance of devices with an optimum composition of 30:70 PBDTTT-CT:PDI. By adding 0.4 vol % of 1,8-diiodooctane we verify the plasticization of the polymer side chains that balances the charge transport properties of the PBDTTT-CT:PDI composite and results in additional improvement in the device efficiency. The temperature-dependent spectral width of the PDI excimer PL band suggests the presence of energetic disorder in the PDI excimer excited state manifold.
Keywords: Charge transfer; Energy transfer; Excimer dissociation; Fullerene-free OPVs; Nonfullerene acceptors; Perylene diimide; Self-assembly